Trinity Cathedral, Trinidad. - Strong (Davidson and Todd Ltd., Trinidad, 2010)
Image depicts the Trinity Cathedral in Port of Spain Trinidad, in the Republic of Trinidad and Tobago. The view is from an area just inside of the north eastern corner of Hart and Frederick Streets looking in a south westwardly direction.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings